2017
DOI: 10.1051/0004-6361/201731020
|View full text |Cite
|
Sign up to set email alerts
|

Radial distribution of dust, stars, gas, and star-formation rate in DustPedia face-on galaxies

Abstract: Aims. The purpose of this work is the characterization of the radial distribution of dust, stars, gas, and star-formation rate (SFR) in a sub-sample of 18 face-on spiral galaxies extracted from the DustPedia sample. Methods. This study is performed by exploiting the multi-wavelength, from ultraviolet (UV) to sub-millimeter bands, DustPedia database, in addition to molecular ( 12 CO) and atomic (Hi) gas maps and metallicity abundance information available in the literature. We fitted the surface brightness prof… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
145
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 131 publications
(163 citation statements)
references
References 189 publications
17
145
1
Order By: Relevance
“…Calistro Rivera et al (2018) showed how the (apparent) compactness of the dust can be explained by a radial decrease of the gas column density and dust temperature toward the outskirts of the sources, on the basis of a radiative transfer model presented by Weiß et al (2007). It is interesting to note that Casasola et al (2017), analysing the gas and dust distribution of a sample of 18 nearby face-on galaxies, found that -on average-the exponential scale-length of the dust-mass surfacedensity is ∼2.3 times higher than that of the molecular gas, that is the dust is distributed at larger radii than the molecular gas, contrary to what we found at high-z. However, we point out that given the sensitivity limit of our observation it is possible that we are tracing only the innermost, warmer phase of dust, whose emission flux increases linearly with the density and temperature (in the Rayleigh-Jeans regime, assuming a constant dust mass).…”
Section: Source Sizecontrasting
confidence: 98%
“…Calistro Rivera et al (2018) showed how the (apparent) compactness of the dust can be explained by a radial decrease of the gas column density and dust temperature toward the outskirts of the sources, on the basis of a radiative transfer model presented by Weiß et al (2007). It is interesting to note that Casasola et al (2017), analysing the gas and dust distribution of a sample of 18 nearby face-on galaxies, found that -on average-the exponential scale-length of the dust-mass surfacedensity is ∼2.3 times higher than that of the molecular gas, that is the dust is distributed at larger radii than the molecular gas, contrary to what we found at high-z. However, we point out that given the sensitivity limit of our observation it is possible that we are tracing only the innermost, warmer phase of dust, whose emission flux increases linearly with the density and temperature (in the Rayleigh-Jeans regime, assuming a constant dust mass).…”
Section: Source Sizecontrasting
confidence: 98%
“…From the abundance of different SFR tracers (e.g. Hao et al 2011;Cortese et al 2012;Lee et al 2013;Boquien et al 2016;Casasola et al 2017), in this study, we are focusing on a reliable single MIR band SFR tracer (Calzetti et al 2010;Cluver et al 2017). Fig.…”
Section: Physical Properties and Dust Scaling Relationsmentioning
confidence: 99%
“…We also selected these galaxies to be roughly representative of early-, mid-, and late-type barred spirals, with the basic properties of each galaxy given in Table 1. For two of them (NGC 1365 and M 83) a detailed analysis of the radial distribution of stars, gas, dust, and SFR is presented in Casasola et al (2017). NGC 1365 ( Fig.…”
Section: Galaxy Sample and Datamentioning
confidence: 99%